Confinement efficiency of concrete cylinders wrapped with different types of frp under impact loads - Pham, Thong; Hao, Hong (2017)
© 2017 Taylor & Francis Group, London. This study investigates the impact resistance of Fiber Reinforced Polymer (FRP) confined concrete cylinders. Concrete cylinders were wrapped with Carbon FRP (CFRP) or Glass FRP (GFRP) with a varied number of layers. The dynamic behavior of the specimens has been examined by using a drop-weight apparatus at different impact velocities. The progressive failure of FRP-confined concrete is studied, which is significantly different from static tests. The dynamic rupture strain of FRP was found to be substantially lower than that under static load. As a result, the FRP efficiency factors were found as 0.56 and 0.18 for GFRP and CFRP, respectively. In addition, although GFRP has lower mechanical properties than those of CFRP, it showed much better performance against impact as compared to CFRP in terms of both strength and ductility. GFRP is more ductile than CFRP so that GFRP could absorb more impact energy and yields higher impact force than CFRP. Therefore, GFRP is probably a better choice than CFRP for strengthening concrete columns against impact loads.